2019
DOI: 10.1111/jcpp.13020
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Does late‐onset attention‐deficit/hyperactivity disorder exist?

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is conceptualized as an early onset childhood neurodevelopmental disorder. Prevalence in adults is around two-thirds that in childhood, yet longitudinal outcome studies of children with ADHD found a minority continue to meet full criteria in adulthood. This suggests that not all adult cases meet ADHD criteria as children, a conclusion supported by earlier studies relying on retrospective recall in adolescent and adult samples. More recently prospective follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
85
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 61 publications
(106 reference statements)
2
85
0
7
Order By: Relevance
“…Interestingly, several recent longitudinal studies adopted a developmental life-course perspective to assessing ADHD and identified an apparent "late-onset" form of ADHD where ADHD symptoms were not reported in childhood but emerged newly in adolescence or adult life [46]. These individuals would not meet current diagnostic criteria for ADHD if their age-at-onset was known and the discovery of this group challenges the conceptualization of ADHD as a neurodevelopmental disorder.…”
Section: Adhd: What Happens Over Timementioning
confidence: 99%
“…Interestingly, several recent longitudinal studies adopted a developmental life-course perspective to assessing ADHD and identified an apparent "late-onset" form of ADHD where ADHD symptoms were not reported in childhood but emerged newly in adolescence or adult life [46]. These individuals would not meet current diagnostic criteria for ADHD if their age-at-onset was known and the discovery of this group challenges the conceptualization of ADHD as a neurodevelopmental disorder.…”
Section: Adhd: What Happens Over Timementioning
confidence: 99%
“…The first study to address this question showed, astonishingly, that 90% of the adults who were diagnosed with ADHD had no history of the disorder during childhood. Perhaps even more astonishingly, this finding was soon replicated in a series of studies reviewed by Asherson and Agnew‐Blais () that reported that anywhere from <1% to 10% of ADHD cases emerge in adolescence and adulthood.…”
mentioning
confidence: 84%
“…The new evidence that ADHD can emerge later than childhood comes with several questions (Castellanos, ; Caye, Sibley, Swanson, & Rohde, ; Faraone & Biederman, ; Shaw & Polanczyk, ). The review by Asherson and Agnew‐Blais () is timely in providing a detailed description of the data on which the findings are based and a thoughtful discussion of whether late‐onset ADHD is likely to be a real phenomenon as opposed to a methodological artifact.…”
mentioning
confidence: 99%
See 2 more Smart Citations